The Effect Of Work From Home (WFH) And Compensation On Employee Productivity During The Covid-19 Pandemic - Khoirunnisah, Asra Ike; Siregar, Onan Marakali (SEAN Institute, 2023)
The state of the pandemic has caused several government policies that have limited public activities in interacting. This certainly has an impact on various sectors of the company. The impact that can be felt by the company is the implementation of WFH in its operational activities. With the existence of WFH, companies make decisions to reduce the compensation. This has an impact on employee productivity. Therefore, the BPJS Employment of the Sumbagut Regional Office must pay attention to the implementation of WFH and the provision of compensation properly so that employee performance gets better. This study aims to determine the effect of WFH and compensation on employee productivity at the Employment of BPJS Ketenagakerjaan Kanwil Sumbagut. This study uses quantitative methods involving 30 employees as a sample. The sampling technique is saturated sampling. Data collection techniques using a questionnaire using a Likert scale. The data analysis technique used instrument test of validity, reliability, classical assumption test, and hypothesis test using multiple linear regression analysis using SPSS. The results of this study indicate that the WFH and compensation variables significantly and simultaneously affect employee productivity. The influence given by the WFH and Compensation variables contributed 41.2% to the employee productivity variable.